PTB domain and leucine zipper motif 1 (APPL1) inhibits myocardial ischemia/hypoxia-reperfusion injury via inactivation of apoptotic protease activating factor-1 (APAF-1)/Caspase9 signaling pathway. Issue 1 (1st January 2021) - Bai, Lina; Yang, Junhua; Zhang, Hong; Liao, Wei; Cen, Yunguang
ABSTRACT: Myocardial ischemia/hypoxia-reperfusion injury mediates the progression of multiple cardiovascular diseases. It has been reported that knockdown of adaptor protein containing a PH domain, PTB domain and leucine zipper motif 1 (APPL1) is a significant factor for the progression of myocardial injury. However, the role of APPL1 in myocardial ischemia remains unclear. Hence, the aim of the present study was to investigate the specific mechanism underlying the role of APPL1 in myocardial ischemia. In our study, the mRNA level of APPL1 was detected by quantitative real-time PCR (RT-qPCR). The expressions of APPL1, Apoptotic protease activating factor-1 (APAF-1), cleaved caspase9 and other inflammation- and apoptosis-related proteins were determined by western blotting. The secretion of inflammatory cytokines and lactate dehydrogenase (LDH) levels were measured by commercial assay kits. The H9C2 cell viability was analyzed by cell counting kit-8 (CCK-8) assay. The apoptosis rate of H9C2 cells was analyzed by TUNEL assay. The interaction between APPL1 and APAF-1/caspase9 was determined by Immunoprecipitation (IP). Our findings demonstrated that APPL1 was low expressed in myocardial ischemia tissues and cells. APPL1 knockdown suppressed the viability of myocardial ischemia cells and aggravated hypoxia/reperfusion-induced LDH hypersecretion, inflammation and apoptosis. In addition, the overexpression of APPL1 induced inactivation of APAF-1/Caspase9 signaling pathway. Significantly, APAF1 inhibitor reversed the effect of APPL1 knockdown on viability, LDH secretion, inflammation and apoptosis. We conclude that APPL1 inhibits myocardial ischemia/hypoxia-reperfusion injury via inactivation of APAF-1/Caspase9 signaling pathway. Hence, APPL1 may be a novel and effective target for the treatment of myocardial ischemia. GRAPHICAL ABSTRACT: uf0001